The stand-in - Bryan, Robbie; Ripa, Kelly; Monticello, Roberto; Good To Be Seen Films; Brentwood Home Video (Firm) ([United States] : Good To Be Seen Films : Brentwood Home Video, 2004)
Robbie Bryan plays Brian Roberts, a man with a promising law career ahead of him, a beautiful girlfriend and a loving family, risks everything to follow his dream of becoming an actor. Based on the true story of actor Robbie Bryan's endeavor to make it as an actor in Hollywood.
Originally produced as a motion picture in 1998.
Special features: cast interviews, lost/deleted scenes, blooper/outtake reel, original theatrical trailer, scene selections.
Robbie Bryan, Kelly Ripa, Lou Myers, Judith Ivey, David Ogden Stiers, Ayo Haynes.
MPAA rating: PG.
DVD; Dolby digital.
Soundtrack: English (2.0 stereo).
Keywords: Actors -- Drama; Acting -- Drama; Comedy films